The Effect of Application Mode and Aging on the Micro-tensile Bond Strength of Universal Adhesives to Enamel of Primary Teeth - Hamdy, Dina Hassan Salaheldeen; Justus Liebig University Giessen (My University, 2026)
The increased demand for simple and efficient adhesive systems made current multimode universal adhesives of great interest in pediatric dentistry. These are mainly characterized by a reduction in the number of application steps, hence limiting the duration of treatment during restorative procedures, together with achieving good dentin adhesion. However, application protocols for universal adhesives have not been defined precisely for primary enamel. Furthermore, the effect of aging was ignored, which lead to reporting higher bond strength values than the real ones due to overlooking the effect of factors, such as thermal stresses and normal daily functions on the bond strength. Thus, the aim of this study was to evaluate the effect of selective acid etching, different etching times, and active rubbing of universal adhesives on the microtensile bond strength to the enamel of primary teeth and to determine the stability of selective acid etching after 6 months aging in an aqueous solution. Sound human primary molars were sectioned mesiodistally. Tooth halves (n=113) were randomized into 3 groups based on the adhesive used: SU: Scotchbond Universal (3M); CU: Clearfil Universal Bond Quick (Kuraray Noritake); iBU: iBond Universal (Heraeus Kulzer). Aprismatic enamel was removed, then groups were subdivided according to application mode into 4 subgroups (SG): SGA: self-etch mode, SGB: 30s-selective etching, SGC: 15s-selective etching, SGD: active rubbing of the adhesive. Adhesives and composite were added (Filtek Z250, 3M). Samples were incubated in distilled water at +37°C for 24h, while separate samples for SGA& SGC were aged for 6 months. Specimens were dissected into rods (0.7 mm × 0.7 mm; IsoMet Highspeed Pro, Buehler), then tested for microtensile bond strength (µTBS; TC-550, Syndicad). Failure patterns were evaluated under light microscope (AZ100M, Nikon). Data were analysed with linear mixed effects model (restricted maximum likelihood, REML) and Sidak post-hoc-tests using SPSS 26.0 (Statistical Packages for Social Sciences, IBM Statistics, Armonk, NY, USA) with significance level set at α < 0.05. Our results showed that selective-etching increased µ-TBS of universal adhesives to primary enamel (p < 0.001) without significance between enamel etching for 15 s and 30 s (p > 0.05). Six-month aging significantly reduced the µ-TBS of SU in SGC (p = 0.014) compared to µ-TBS after 24h incubation. So, it was concluded that, selective etching with phosphoric acid remains the gold standard for bonding universal adhesives to primary enamel. Etching time showed no significant effect on µ-TBS. Aging may affect the µ-TBS of SU applied on 15 s phosphoric acid etched primary enamel.
Keywords: ddc:610